2020
DOI: 10.3390/polym12122916
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Bioactive Compounds from Jaboticaba Peels and Application into Zein Ultrafine Fibers Produced by Electrospinning

Abstract: This work focused on the recovery bioactive compounds from jaboticaba peels and to develop ultrafine fibers from zein incorporated with the jaboticaba extract by electrospinning technique. Jaboticaba peel extracts (JPE) were obtained by maceration according a central composite rotational design (CCDR) and characterized with respect to total phenolic content (TP), antioxidant activity (AA) and total anthocyanin (TA). The optimal condition for the extraction was obtained using a desirability function in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…According to what was expected, this signal was less intense in the films containing JPE than the freeze-dried extract. Similar results were obtained by Avila et al [16], who reported the same behavior in ultrafine fibers produced with different concentrations of freeze-dried jaboticaba peel extract. Comparing the JPE containing films with the control film, it was possible to observe a band shift of 3300 for higher wavenumbers as JPE is added.…”
Section: Carrageenan Film Characterizationsupporting
confidence: 90%
See 1 more Smart Citation
“…According to what was expected, this signal was less intense in the films containing JPE than the freeze-dried extract. Similar results were obtained by Avila et al [16], who reported the same behavior in ultrafine fibers produced with different concentrations of freeze-dried jaboticaba peel extract. Comparing the JPE containing films with the control film, it was possible to observe a band shift of 3300 for higher wavenumbers as JPE is added.…”
Section: Carrageenan Film Characterizationsupporting
confidence: 90%
“…Then, the jaboticaba peel extract was obtained by maceration according to the optimal condition described by Avila et al [16] using acidified water (pH 1) as solvent and extraction temperature of 88 • C for 1 h. These parameters were defined according to an experimental design that evaluated the parameters of extraction temperature and solvent pH for the recovery of total phenolic compounds and total anthocyanin from freeze-dried jaboticaba peels. The extraction step was performed in a water-bath (SOLAB-SL 157, Piracicaba, Brazil) under constant agitation.…”
Section: Extract Preparationmentioning
confidence: 99%
“…However, the increase of fiber diameter was attributed to the higher solution viscosities [31]. Meanwhile, a contrary effect was obtained in the study of Avila et al In this case, the incorporation and increase of jaboticaba peel extract concentration into zein solutions increased their electrical conductivity, which favored the formation of thinner fibers [35]. The same effect was also evidenced in the electrospinning process of chitosan nanofibers loaded with lysozyme [42].…”
Section: Electrical Conductivitymentioning
confidence: 90%
“…A work about PCL fibers loaded with sage extract evidenced that the incorporation and increase of extract concentration in the polymeric solution decreased its viscosity and favored the production of thinner fibers [33]. Likewise, an increase of concentration of jaboticaba peel extract in a zein solution decreased its viscosity and the diameter of the fibers [35]. Meanwhile, an increase of concentration of tomato peel extract in a polymeric solution of zein produced an increase of its viscosity and the development of thicker fibers [34].…”
Section: Viscositymentioning
confidence: 99%
“…Despite this, superior electrical conductivity poses difficulties since the solution does not possess adequate charge repulsion to overcome its surface tension [66]. Several studies have reported an increase in conductivity upon incorporating anthocyanin into the polymer solution and higher elongation of jet and fibers with a smaller diameter [67][68][69].…”
Section: Electrospraying/electrospinningmentioning
confidence: 99%